Efficient (k, n) threshold semi-quantum secret sharing protocol - Cao, Jie; Xu, Jinchao (Frontiers in Physics, 2025)
Most (k, n) threshold quantum secret sharing protocols are fully quantum. The message receivers must be equipped with complex quantum devices so as to prepare various quantum resources and perform complex quantum operations, which may affect the practice of these protocols. On the other hand, the qubit efficiency of most (k, n) threshold quantum secret sharing protocols is not more than 1/2. To simplify the (k, n) threshold quantum secret sharing protocol and improve its practice and qubit efficiency, a new (k, n) threshold secret sharing protocol with semi-quantum properties is proposed. In this protocol, the dealer prepares decoy particles and sends them to the receivers. The receivers insert particles carrying secret information along with Z-basis decoy particles into the received particle sequence to generate mixed-particle sequences, which are returned to the dealer. The dealer measures the received particle sequences to check for eavesdropping and establishes shared secret keys with the receivers. With the shared secret keys, the dealer distributes the secret pieces among the receivers using Shamir’s secret sharing scheme. Multiple secret messages can be recovered by k or more receivers. The qubit efficiency of our protocol is k/n. For an (n, n) threshold protocol, the qubit efficiency would be 100%. The proposed scheme is based on single particles without using any entangled system. Therefore, its quantum resources are relatively easy to prepare. Receivers must only prepare simple Z-basis qubits. Its semi-quantum properties enhance practice implementation. The proposed protocol has robust security against various types of attacks, including eavesdropping, internal, and collusion attacks. Furthermore, it can resist the unitary attack, which is seldom analyzed in other protocols.